INTEGRASI KOMPETENSI NONTEKNIS DALAM EMPLOYABILITY: ANALISIS PLS-SEM ATAS SOFT SKILL, MOTIVASI KERJA, DAN KESIAPAN KERJA - Shofaa' Najwan; Nada Shofa Lubis; Didik Iskandar (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the influence of soft skills and work motivation on the job readiness of engineering students at Universitas Cendekia Abditama Tangerang. Job readiness is an important issue in higher education because graduates are expected to master technical competencies while also showing adaptability, responsibility, communication, teamwork, and internal motivation to meet workplace demands. This research used a quantitative approach with an explanatory design. The population consisted of 44 sixth-semester students of the Informatics System Study Program, Faculty of Engineering, and all students were selected as respondents using a saturated sampling technique. Data were collected through a five-point Likert scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings show that soft skills have a positive and significant effect on job readiness. Work motivation also has a positive and significant effect on job readiness. Simultaneously, both variables explain 64.7% of job readiness variance, with soft skills as the dominant predictor for improving graduate employability within structured higher education learning programs today effectively overall.